(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
From June to September 1999 samples of leaves infested by Citrus Leaf Miner (CLM) Phyllocnistis citrella Stainton were collected in citrus groves around Palermo, Agrigento, Trapani and Linosa Island in order to bred its Eulophid parasitoids. Asecodes delucchii (Boucek), A. erxias (Walker), Cirrospilus diallus Walker, C. pictus (Nees), C. vittatus Walker, Pnigalio agraules Walker and Semilacher petiolatus (Girault) emerged. S. petiolatus has been found in ali the citrus groves investigated, except the one located at Trapani territory. Furthermore its relative abundance was much higher than the ali other species together in the localities where these latters emerged. During the investigations it was observed that 4th CLM instar larvae may also be parasitized by S. petiolatus. These records on this wasp look not only at its definitive establishment, but at its recovery also into the biologica! niche previously occupied by severa! indigenous CLM’ parasitoids.